Pengaruh Kompensasi, Motivasi, dan Loyalitas Kerja Terhadap Kinerja Karyawan Restoran Gurih 7 Bogor Pada Masa Pandemi Covid-19 - Suparno, Suparno; Ramly, Amir Tengku; Rahim, Anwar (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2022)
This study aims to determine the effect of compensation, motivation, and work loyalty on the performance of employees at Gurih 7 Restaurant Bogor. Data collection through questionnaires and data analysis techniques used in this study is a quantitative method with the help of the SPSS 22.0 program. The rating system used in this study is a Likert scale. This study uses multiple linear regression analysis. The population in this study were all restaurant employees, totaling 34 people. The sampling technique in this study used the slovin formula. The results of the study concluded that compensation has no positive and significant effect on employee performance. Motivation has no positive and significant effect on employee performance. Work loyalty has a positive and significant effect on employee performance.